Immersive virtual reality in K‐12 and higher education: A 10‐year systematic review of empirical research - Di Natale, Anna Flavia; Repetto, Claudia; Riva, Giuseppe; Villani, Daniela (British journal of educational technology, 2020)
Immersive Virtual Reality (IVR) systems offer several learning affordances, that is, characteristics that can elicit learning behaviors promoting learning outcomes in educational contexts. In particular, the immersive and interactive properties of these systems represent a strong opportunity to support the effective learning experiences. The present review aims at mapping IVR systems’ use in K‐12 and higher educational contexts and investigating their effectiveness in facilitating learning in terms of knowledge attainment and retention and motivational outcomes. The synthesis of the reviewed studies (n = 18) show that IVR can support a number of activities and experiences that in turn improve learning and motivate students to fulfill educational goals by eliciting their interest and engagement with the learning materials. The main advantage of IVR seems related to the possibility for users to have first‐hand experiences that would not be possible in the real world, simultaneously offering unique opportunities for experiential and situated learning, as well as promoting students’ motivation and engagement. Despite the promising findings, the reviewed studies present several methodological flaws: non‐randomized trials, small sample sizes, unbalanced samples and non‐validated measures. This in turn makes it difficult to generalize from these results. Future research is needed to investigate the unique opportunities of IVR in education.